Influence of renal function and demographic data on intrarenal Doppler ultrasonography - Abe, Michiaki (PLoS One, 2019)
Intrarenal Doppler ultrasonography is a non-invasive method to evaluate the renal blood flow in patients with renal arterial stenosis as well as chronic kidney diseases (CKD). Until recently, the relationship between ultrasonography findings and CKD stage has not been fully understood. Overall, 162 patients with CKD without apparent renal arterial stenosis were included in this study, and the pulsed-wave Doppler ultrasonography findings were evaluated in terms of the following parameters: peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistive index (RI) at the renal arterial trunk, hilum, segmental, and interlobar regions. Age showed a significant negative correlation with the estimated glomerular filtration rate (eGFR), kidney size, and aortic PSV. Additionally, age showed a significant positive correlation with RI in all 4 regions. The eGFR showed a positive correlation with the aortic PSV and kidney size, but a negative correlation with RI. Both age and eGFR were found to be independently associated with aortic blood flow. On the intrarenal ultrasound, EDV and RI showed stronger correlations with eGFR than PSV, suggesting that the former indices would be better markers of renal function. In particular, the interlobar EDV was found to be the best index that reflects renal function. Although the RI is also a good marker of renal function, it is confounded by age; thus, its utility would be weaker than that of the EDV. In conclusion, intrarenal pulsed-wave Doppler ultrasonography is a useful tool to estimate and evaluate the renal function; the interlobar EDV may be the best index to estimate the effective perfusion and filtration of the kidneys.